EXPLORING THE GENETIC DIVERSITY AND PHYLOGENY OF FOUR NATIVE WILD DEER SPECIES OF PAKISTAN USING MITOCHONDRIAL MARKERS - Ghulam Abbas; Asif Nadeem; Masroor Ellahi Babar; Raja Danish Muner; Ali Haider Saleem; Babar Maqbool; Yanzhen Bi; Shahzad Akbar Khan; Farhan Farooq; Mujtaba Shahid (Journal of Animal and Plant Sciences, 2026)
Bovidae and Cervidae are the most important families of mammals. Owing to extensive human interference, excessive use of natural resources, unregulated hunting, and other adverse environmental conditions, some of these wild species are now facing the risk of extinction. Genetic variation underpins animal survival from an evolutionary perspective, which is vital for the conservation of animals, particularly endangered species that, if not protected, will soon become extinct. Therefore, the current study was planned to investigate the molecular phylogeny and genetic diversity of Bovidae (Boselaphus tragocamelus, Antilope cervicapra) and Cervidae (Axis axis, Axis porcinus) families of wild deer in Pakistan using the collective effect of mitochondrial cytochrome b, cytochrome c oxidase subunit 1 (Cox1), and D-loop regions. For the genetic diversity study, we collected blood samples from unrelated wild deer of all four species (n=100; 25 per species) in EDTA-containing vacutainers. Genomic DNA was extracted using the phenol-chloroform method. PCR was performed to amplify the cytochrome b, Cox1, and D-loop genes, and the PCR products were sequenced in Foster City, CA, USA. In this study, we found evidence of a significant reduction in genetic diversity among members of Bovidae and Cervidae from different regions of Pakistan. The findings of the current study revealed the genetic distinctness of the studied wild deer species and their evolutionary divergence. Moreover, native deer populations exhibited reduced within-population genetic variability; therefore, a viable conservation plan is needed to ensure their survival and protection under changing environmental conditions.
Keywords: Genetic diversity; Wild deer; Cytochrome b; Cox1; and D loop